Media's Investments in Untruths - Lee, Micky. author. aut Link
IX, 89 p.
Keywords: This book examines the gendered nature of business fraud by examining media representations of four entrepreneurs (Sam Bankman-Fried, Elizabeth Holmes, Bernie Madoff, and Anna Sorokin) who swindled money from wealthy investors and everyday people. From a feminist political economic perspective, the book asks how the intersections between gender, age, socioeconomic background, and the country of origin matter in media portrayals. By examining fictionalized television shows, films, and news reports about the four fraudsters, the book considers: what kinds of “truth” do media texts unveil through story narrative, character development, and mise-en-scene? How were financial crimes seen to disrupt an orderly and rational market? How were fraudsters redeemed or not in media texts? This book will interest media studies scholars who examine gender, finance, and economics. Micky Lee is a Professor of Media Studies at the Communication, Journalism, and Media Department at Suffolk University, Boston. Her research areas are feminist political economy; finance, information and technologies; and Asian popular culture. She has published more than ten books, and over 40 journal articles, book chapters, and essays. Her book, Bubbles and Machines (2019), examines the gender nature of financial crisis by analyzing Hollywood and documentary films, popular fictions, and historical texts. She has published three journal articles and one book chapter about gender and finance in popular media.